BARRIER FACTORS AFFECTING DEVELOPMENT OF INTELLIGENT TRANSPORT SYSTEM PROJECTS - Nguyen, Phong Thanh; Nguyen, Thu Anh; Tran, Thang Huynh Tat (Journal of process management and new technologies, 2021)
This paper identifies potential barrier factors affecting effectiveness and development (ED) of ITS projects as well as criteria for measuring ED of ITS projects in Ho Chi Minh City, Vietnam. The study discovers the barrier constructs, and analyzes data using the Partial Least Squares Structural Equation Modeling method (PLS-SEM). The results provides a general and comprehensive overview of the main issues of ITS, and identifies 28 barrier factors with five main constructs affecting ED of ITS projects, namely the lack of undivided attention from the government (AG), financial constraints for ITS (FC), inadequate transport infrastructure (ITI), the over-development of urbanization (ODU), and the readiness and integration for ITS (RI). This paper fill the knowledge gap by discovering the causal relationships between barrier constructs and ED of ITS projects in Vietnam. Also it proposes several solutions for these issues, which are also a useful measurement tool for government agencies, planners, and traffic system designers to help them self-assess and make action plans now or in the near future.
Keywords: Barrier Factors, PLS-SEM, Intelligent Transport Systems (ITS), Smart City, Vietnam